Improvement of Solar Energy Conversion with Nb‐Incorporated TiO2 Hierarchical Microspheres. Issue 10 (19th March 2013) - Hoang, Son; Ngo, Thong Q.; Berglund, Sean P.; Fullon, Raymond R.; Ekerdt, John G.; Mullins, C. Buddie
Abstract Niobium‐modified TiO2 hierarchical spherical micrometer‐size particles, which consist of many nanowires, are synthesized by solvothermal synthesis and studied as photoelectrodes for water photo‐oxidation and dye‐sensitized solar cell (DSSC) applications. Incorporation of Nb leads to a rutile‐to‐anatase TiO2 phase transition in the TiO2 hierarchical spheres (HSs), with the anatase percentage increasing from 0 % for the pristine TiO2 HSs to 47.6 % for the 1.82 at. % Nb‐incorporated TiO2 sample. Incorporation of Nb leads to significant improvements in water photo‐oxidation with the photocurrents reaching 70.5 μA cm−2 at 1.23 V versus the reversible hydrogen electrode, compared with 28.3 μA cm−2 for the pristine TiO2 sample. The photoconversion efficiency of Nb:TiO2 HS‐based DSSCs reaches 6.09±0.15 % at 0.25 at. % Nb, significantly higher than that for the pristine TiO2 HS cells (3.99±0.02 %). In addition, the incident‐photon‐to‐current efficiency spectra for DSSCs show that employing TiO2 and Nb:TiO2 HSs provides better light harvesting, especially of long‐wavelength photons, than anatase TiO2 nanoparticle‐based DSSCs.